Squamous cell carcinomas in chronic venous leg ulcers. Data of the German Marjolin Registry and review. (October 2015) - Reich‐Schupke, Stefanie; Doerler, Martin; Wollina, Uwe; Dissemond, Joachim; Horn, Thomas; Strölin, Anke; Erfurt‐Berge, Cornelia; Stücker, Markus
Summary Background Secondary squamous cell carcinoma (SCC) is a rare complication of chronic venous leg ulcers. So far, little is known about its pathophysiology and clinical behavior. Initiated by the working group "Wound Healing" (AGW) of the German Society of Dermatology (DDG), it is the objective of the current Marjolin registry to collect cases of SCC arising in venous ulcers, in order to evaluate diagnostic characteristics. Patients and Methods All members of the AGW received questionnaires inquiring about basic patient data, ulcer characteristics, and therapy conducted. Results From 2010 to 2013, 30 patients (20 women, 10 men) from six tertiary wound care centers were registered. Mean age was 76.17 years. The average duration of venous leg ulcers prior to SCC diagnosis was 15.93 years. Suspicious wound characteristics primarily included: pain (n = 3), therapy resistance (n = 27), and fetor (n = 12) as well as clinical appearance (n = 10) with atypical morphology, nodular wound bed, and hypergranulation. Conclusions Atypical morphology or changes in appearance as well as therapy resistance despite optimal care (6–12 weeks) should prompt physicians to take spindle‐shaped, if necessary multiple and serial, biopsies. Primary risk factors for malignant transformation include patient age and ulcer duration.